Editorial Volume 6, Issue 2 - Kristy L Archuleta (Journal of Financial Therapy, 2016)
Money scripts, money behaviors, money disorders, and financial coaching have been seen in recent popular press. If you are reading this issue, you are probably aware that continued empirical research in these areas is needed. I am pleased to introduce the articles related to these topics in this issue of the Journal of Financial Therapy.
Keywords: editorial; financial therapy